Ketika al-Qur’an Bertemu Modernitas: Penerimaan Pemikir Kontemporer Islam dalam Konteks Kebebasan Beragama - Hakim, Moh. Arif Rakman (Contemporary Quran, 2024)
The renewal concepts offered by contemporary Indonesian thinkers on actual issues involve legitimizing their views through the Quran. The approach of validating these issues, such as religious freedom, using various Quranic verses showcases a range of interpretations that can appear subjective and arbitrary. This research seeks to uncover the dialectical relationship between contemporary Indonesian thinkers, specifically Nurcholis Madjid, Abdurrahman Wahid, and Djohan Effendi, and the Quran, which forms a response of meaning to address current issues. Employing a qualitative methodology, the study utilizes Hans Robert Jauss’reception theory for data analysis. The findings indicate that the tendency to use the Qur'an in addressing actual issues is grounded in the compatibility of meaning, using the keywords within the verses that align with the issues being discussed. When suitable keywords are identified in a verse, they are interpreted with a dominance of the initial impression of understanding, primarily based on their linguistic meanings. This uniformity in meaning perception, which emphasizes objective meaning through language, is then applied to the contemporary context. The perception of liberal interpretation arises because the traditional interpretative moment, which mediates various perspectives of past interpreters, is often bypassed. As a result, these interpretative efforts cannot be fully categorized under the concept of contextual interpretation. However, the determination of objective meaning through textual analysis, extended to a new context that incorporates the subjective experiences of each thinker, makes this understanding mechanism not as subjective as commonly assumed.